Adrenocorticotropic Hormone-Producing Paraganglioma With Low Plasma ACTH Level: A Case Report and Review of the Literature - Liu, Siyue; Liu, Zhelong; Chen, Fuqiong; Xu, Weijie; Yuan, Gang (Frontiers in Endocrinology, 2020)
Ectopic adrenocorticotropic hormone (ACTH) syndrome caused by paraganglioma is extremely rare. It usually accompanied by high or normal plasma ACTH level. Here we described a male who presented with ectopic ACTH-producing paraganglioma and a low plasma ACTH level. Immunohistochemistry and immunofluorescence confirmed ACTH production in focal paraganglioma cells. This unusual case expanded the spectrum of ACTH-dependent Cushing's syndrome and revealed a potential mechanism of this unique clinical phenotype. Besides, the literature concerning ACTH-producing paraganglioma is reviewed.